2015
DOI: 10.5588/ijtld.14.0301
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of tuberculosis in haematopoietic stem cell transplant recipients: a 10-year nationwide study

Abstract: HSCT is associated with an increased risk of TB in endemic regions. Older age and development of chronic GVHD are independent predictors of late onset active TB in HSCT recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 0 publications
3
36
1
1
Order By: Relevance
“…Tuberculosis is an opportunistic infection seen in hematopoietic stem cell transplantation recipients. Risk of TB infection might vary with respect to underlying illness, pretransplantation conditioning, T‐cell depletion, comorbid conditions, presence of GVHD, and corticosteroids and other immunosuppressive agents . There are guidelines that determine and treat LTBI with targeted TST in patients at risk .…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is an opportunistic infection seen in hematopoietic stem cell transplantation recipients. Risk of TB infection might vary with respect to underlying illness, pretransplantation conditioning, T‐cell depletion, comorbid conditions, presence of GVHD, and corticosteroids and other immunosuppressive agents . There are guidelines that determine and treat LTBI with targeted TST in patients at risk .…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium tuberculosis is an acid-fast, aerobic bacillus, which is one of the leading infectious diseases around the world [1, 2]. Tuberculosis (TB) is also well known for a significant opportunistic infection among hematopoietic stem cell transplantation (HSCT) recipients, although it is 10 times less frequent than in solid organ transplant patients [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis (TB) is also well known for a significant opportunistic infection among hematopoietic stem cell transplantation (HSCT) recipients, although it is 10 times less frequent than in solid organ transplant patients [2, 3]. The immune system of HSCT recipients are suppressed as a result of their hematologic diseases, chemotherapy, radiation, immunosuppressive therapy, and graft-versus-host disease (GVHD) [1]. Thus, the incidence of TB among allogeneic HSCT recipients is reportedly 2–40 times higher than that of the general population [1, 4–6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10-year retrospective review in an endemic area also found a low proportion of extrapulmonary manifestations (5 compared with 34 pulmonary involvement alone). 3 Risk factors for tuberculosis infection identified in the literature include T-cell depletion, matched unrelated donors, use of steroids, conditioning regimens and underlying malignancy. 4 Making the diagnosis can be difficult in a post allogeneic stem cell transplant patient due to the atypical clinical manifestations including fever of unknown origin, acute respiratory distress syndrome, acute kidney injury and cholestatic jaundice.…”
mentioning
confidence: 99%